Dieletric Strength of Waste Tyre-Dust-Polypropylene (WTD-PP) for High oltage Application - Aman, Aminudin; Yaacob, Mohd Muhridza; ABD RAZAK , JEEFFERIE (AENSI, 2011)
Abstract: This paper examines the performance of Waste Tyre Dust-Polypropelene (WTD-PP) composite with Alumina Trihydrate (ATH) as the main reinforcement filler for high voltage outdoor insulation material. Compounds of WTD-PP without and with ATH were prepared with different compositions of WTD-PP content (20/80, 40/60,60/40,80/20wt%) and different amount of ATH filler (0,50,100,150pph). The parameter studied is dielectric strength of WTD-PP composite and BS EN 60243-1 was complied. It was found that the performance of these compounds as outdoor high voltage insulation application. The volume resistivity as well as dielectric strength of the compounds was reduced due to high content of carbon black into the waste tyre. It also shows the effects of ATH into the compounds and the optimum value the ATH is 100pph.